2015
DOI: 10.1186/s13071-015-0802-9
|View full text |Cite
|
Sign up to set email alerts
|

Low prevalence of blood parasites in a long-distance migratory raptor: the importance of host habitat

Abstract: BackgroundThe low prevalence of blood parasites in some bird species may be related to the habitats they frequent, the inexistence of the right host-parasite assemblage or the immunological capacity of the host. Here, we assess the parasite load of breeding populations of Eleonora’s falcon (Falco eleonorae), a medium-sized long-distance migratory raptor that breeds on small isolated islets throughout the Mediterranean basin and overwinters in inland Madagascar.MethodsWe examined the prevalence and genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…Strong relationships between landscape use and the prevalence of blood parasites infecting birds have previously been shown (Fourcade et al., ; Patz et al., ), which may be due to the effect of landscape features on the vector community (Norris, ). For instance, the scarcity of suitable vectors has been identified as the most likely reason of the low prevalence or absence of Plasmodium in birds from marine and saline environments (Figuerola, ; Gutiérrez‐López et al., b; Martínez‐de la Puente et al., ; Mendes, Piersma, Lecoq, Spaans, & Ricklefs, ) and deserts (Merino, Barbosa, Moreno, & Potti, ). Indeed, environmental characteristics strongly determined the mosquito abundance and community composition in the study area (Ferraguti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Strong relationships between landscape use and the prevalence of blood parasites infecting birds have previously been shown (Fourcade et al., ; Patz et al., ), which may be due to the effect of landscape features on the vector community (Norris, ). For instance, the scarcity of suitable vectors has been identified as the most likely reason of the low prevalence or absence of Plasmodium in birds from marine and saline environments (Figuerola, ; Gutiérrez‐López et al., b; Martínez‐de la Puente et al., ; Mendes, Piersma, Lecoq, Spaans, & Ricklefs, ) and deserts (Merino, Barbosa, Moreno, & Potti, ). Indeed, environmental characteristics strongly determined the mosquito abundance and community composition in the study area (Ferraguti et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…The lineage LK6 was recently isolated from passerines from Macaronesian archipelagoes, the Iberian Peninsula and Morocco (electronic supplementary material, table S1). Although the transmission areas remain unclear, it has been proposed that migratory birds such as Eleonora's falcon could spread blood parasites to resident birds on the main islands, where insect vectors are present [16]. It has been suggested that darker colours are more attractive to mosquitoes than light colours and so entirely dark plumages could increase host-vector contact rates.…”
Section: Discussionmentioning
confidence: 99%
“…In feral pigeons (Columba livia), alternative morphs were distributed non-randomly across an urban gradient and had different parasite risks [15]. However, the different Eleonora's falcon morphs inhabit small islands sympatrically during the breeding season and local transmission of blood parasites at breeding grounds is absent, owing to the lack of suitable vectors [16]. Therefore, differences in the exposure to vectors must occur during migration and/or in their wintering quarters, where rsbl.royalsocietypublishing.org Biol.…”
Section: Discussionmentioning
confidence: 99%
“…To identify the avian hosts of the blood parasites that were isolated from the louse flies, blood samples from both adult and nestling Eleonora's falcons and bird prey were obtained. Blood parasites infecting Eleonora´s falcons that were sampled from 2006 to 2014 ( N = 173 nestlings and 209 samples from 183 adults) had been previously analyzed (Gangoso et al, ; Gutiérrez‐López, Gangoso et al, ). In addition, in September 2013 we sampled 90 recent kills of 12 bird species belonging to seven different families.…”
Section: Methodsmentioning
confidence: 99%
“…The Eleonora's falcon ( Falco eleonorae ) is a medium‐sized long‐distance migratory raptor that breeds on islands in the Mediterranean basin and winters in Madagascar (Kassara et al, ; Walter, ). Adult Eleonora's falcons are commonly infected by Plasmodium and Haemoproteus parasites (Gangoso, Gutiérrez‐López, Martínez‐de la Puente, & Figuerola, ; Gutiérrez‐López, Gangoso et al, ). In addition, both adults and nestlings are heavily parasitized by the louse fly Ornithophila gestroi (Gangoso et al, ), which has only been reported on Eleonora's falcon and the closely related common and lesser kestrels ( Falco tinnunculus and Falco naumanni ) (Beaucournu, Beaucournu‐Saguez, & Guiguen, ; Gangoso et al, ; Walter, ).…”
Section: Introductionmentioning
confidence: 99%